Network Operation,Maintenance and Resource Management in Mega Constellation System - Di ZHOU; Min SHENG; Qi HAO; Jiandong LI; Jianping LIU (天地一体化信息网络)
As the overall scale of the constellation system continues to increase,its service capabilities are gradually expanding from traditional mobile communication services to broadband interconnection services,which puts forward new requirements for the operation,maintenance and resource management in the satellite constellation system.The challenges brought by constellation scale,resource dynamics,and resource failure for the performance management-oriented network operation and maintenance and resource management in mega constellation system (MCS) were fi rst analyzed.The key technologies of network operation,maintenance and resource management for MCS were discussed from the aspects of traff c prediction and resource perception and maintenance and dynamic resource slicing.An intelligent network management and control architecture was proposed to realize lightweight operation and maintenance and resource management for MCS,laying a theoretical foundation for the efficient network operation and maintenance and resource management technology for future space-terrestrial integrated networks.